2020
DOI: 10.3904/kjim.2019.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking on blood lipids in Korean men: Cardiovascular and Metabolic Diseases Etiology Research Center cohort

Abstract: Background/Aims: Cigarette smoking and abnormal blood lipids are major risk factors for cardiovascular disease. The results of previous studies on the relationship between cigarette smoking and dyslipidemia are controversial. In the present study, we investigated the independent association between cigarette smoking and blood lipid levels in a male Korean population. Methods: A total of 1,932 men aged from 30 to 64 years old participated in the Cardiovascular and Metabolic Diseases Etiology Research Center coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
2
11
0
1
Order By: Relevance
“…The significance of smoking and tobacco use in the onset of disordered lipid profile, [38][39][40] CVD risks, 7,41,42 and mortality 3,43 has been well documented in the literature. For example, active smoking and tobacco use have been associated with elevated triglycerides, 39 myocardial injury, 42 and vascular diseases 41 among others. However, the contribution(s) of SHSE, particularly among non-smokers, is yet to be well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of smoking and tobacco use in the onset of disordered lipid profile, [38][39][40] CVD risks, 7,41,42 and mortality 3,43 has been well documented in the literature. For example, active smoking and tobacco use have been associated with elevated triglycerides, 39 myocardial injury, 42 and vascular diseases 41 among others. However, the contribution(s) of SHSE, particularly among non-smokers, is yet to be well documented.…”
Section: Discussionmentioning
confidence: 99%
“…M0 macrophages were reported to be inversely associated with patients' outcomes in various, such as adrenal cortical carcinoma and lung cancer [46,47]. Nowadays, majority studies evaluated the degree of smoking based on the frequency of tobacco use to define heavy smokers and light smokers without uniform quantifying standards [48][49][50]. Moreover, these cut-offs cannot accurately identify the true degree of smoking because they do not comprehensively consider the DNA damage and microenvironment alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is a known behavioral risk factor for hypertriglyceridemia [25][26][27]. We found that the prevalence of hypertriglyceridemia among current smokers, especially among regular current smokers, was higher when compared with those who never smoked.…”
Section: Discussionmentioning
confidence: 78%